From Energy Improvement to Accuracy Enhancement: Improvement of Plate Bending Elements by the Combined Hybrid Method (Journal of Computational Mathematics, 2004)
By following the geometric point of view in mechanics, a novel expression of the combined hybrid method for plate bending problems is introduced to clarify its intrinsic mechanism of enhancing coarse-mesh accuracy of conforming or nonconforming plate elements. By adjusting the combination parameter $α \in (0,1)$ and adopting appropriate bending moments modes, reduction of energy error for the discretized displacement model leads to enhanced numerical accuracy. As an application, improvement of Adini's rectangle is discussed. Numerical experiments show that the combined hybrid counterpart of Adini's element is capable of attaining high accuracy at coarse meshes.